ANALISIS KURIKULUM MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VII MTS AL-IMAM CIKEMBAR SUKABUMI JAWA BARAT - Nur Rahma, Farida; Kusumah, Mada Wijaya; Hidayat, Tatang; Madjid, Abdul (JURNAL KAJIAN ISLAM MODERN, 2025)
The purpose of this study is to analyze the curriculum of Islamic cultural history subjects class VII MTs Al Imam Cikembar Sukabumi. This research uses a qualitative approach and a literature study method. Based on the results of the discussion, the curriculum of the Islamic Cultural History class VII MTs from the aspect of purpose is in accordance with the objectives of MTs nationally, but is not in accordance with the objectives of the MTs Al-Imam institution which emphasizes more on developing the potential of students individually only. In the aspect of teaching materials, the scope of the subject of Islamic Cultural History class VII MTs is the same as the scope of the subject of Islamic Cultural History of Madrasah Ibtidaiyah. In the sequence of teaching materials of SKI class VII MTs is ideal, according to the facts, there is no continuity of teaching material, what happens is the deepening of the teaching material. Mayoritas, keseimbangan dalam aspek isi sudah ideal. In the majority, the balance in the content aspect is already ideal. From the syllabus, it reads that learning strategies tend to be monotonous and still teacher centers. Meanwhile, in the assessment aspect, teachers include all types of assessments.